Rancang Bangun Alat Kompres Demam Digital Suhu Hangat - Bachri, Karel Octavianus; Kevin, Kevin; Sereati, Catherine Olivia (Cylinder : Jurnal Ilmiah Teknik Mesin, 2024)
In this research, a digital fever compress device based on Arduino Uno was designed, utilizing warm temperature as a method for fever management. The device is equipped with a temperature sensor DHT, liquid crystal display (LCD), relay, and cartridge heater to create precise and controlled warm temperatures. The objective of this research is to design a digital fever compress device capable of generating warm temperatures ranging from 37.5°C to 42°C using Arduino Uno as the main microcontroller. The design process involved creating a model of temperature and tension equations, where the influential variables include ambient temperature, upper limit, and lower limit. Result shows the difference of the temperature values over time with the overall standard deviation of 1.4894, 1.6480, and 1.6217 and the overall standard deviation of the maxima and minima of 0.8085. The test results also indicated outcomes beyond the limits due to the large sampling time.